SURVEI TINGKAT PARTISIPASI DAN KEBUGARAN JASMANI MASYARAKAT DALAM PEMBANGUNAN OLAHRAGA DI KABUPATEN PURBALINGGA (Universitas Negeri Semarang, 2020)
The purpose of the study is to find out the participation rate and physical fitness level of the public in Purbalinga Regency toward sport development. The research method uses a survey method and then the sport development index is used later to analyze further. The population of the study is the entire citizen of Purbalingga Regency. The sample is determined by stratified random sampling and cluster sampling, the total is 90 people divided into 3 districts. Each district consisted of 30 people in 3 categories: 10 children, 10 teenagers, and 10 adults with the provisions in each category consisting of 5 men and 5 women. The location of the study is Bojongsari district, Purbalingga district, and Bukateja district. The variables studied in this study are the Sport Development Index of Purbalingga Regency, which is: Participation and Physical Fitness. This study uses an interview instrument, questionnaire, and MFT (Multistage Fitness Test). Data analysis uses primary data that is participation and secondary is population. The results of the study are the participation of the pubic in Purbalingga Regency is 0.53 which means in middle category 1) the citizen perceive that the daily activities are already exhausting 2) the daily activities keep the citizen busy so they don’t have a time to do sport. The physical fitness level of Purbalingga Regency is 0.33 in the low category 1) the daily activities consumed most of the citizen time, energy, and mind 2) the citizen doesn’t have enough time to do sport therefore their fitness and health weaken. The conclusion of this study is the rate of public participation in the middle category because 1) many people already know the benefits and importance of sports for health 2) the availability of facilities and infrastructures such as spaces for sports so the people interested in doing sport activities. While, the level of physical fitness of the community in the low category because 1) many people are tired of their daily activities that affect their physical fitness. Suggestion from the researcher is 1) need to hold an activity that drawn people interest in sport activity 2) to keep maintaining all sports facilities in best condition also built another public sport facilitiy in each district.